Prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome derived from chromosome 3 - Chih-Ping Chen; Tsang-Ming Ko; Chen-Yu Chen; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Chen-Wen Pan; Wayseen Wang (Elsevier, 2019)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of a small supernumerary marker chromosome (sSMC) derived from chromosome 3. Case report: A 36-year-old woman underwent amniocentesis at 19 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XX,+mar[6]/46,XX[18]. The mother's karyotype was 47,XX,+mar[4]/46,XX[46]. The father's karyotype was 46.XY. Array comparative genomic hybridization (aCGH) analysis of uncultured amniocytes revealed a result of arr 3q11.1q12.1 (93,575,285-98,956,687) × 2-3 [GRCh37 (hg19)]. Prenatal ultrasound findings were unremarkable. The parents elected to continue the pregnancy, and a 2470-g female baby was delivered at 37 weeks of gestation without phenotypic abnormalities. The cord blood had a karyotype of 47,XX,+mar[8]/46,XX[32]. aCGH analysis of cord blood revealed a result of arr 3q11.1q11.2 (93,649,973-97,137,764) × 2.4 [GRCh37 (hg19)] with a log2 ratio of 0.25 and a 30-40% mosaicism for 3.488-Mb dosage increase in 3q11.1-q11.2 encompassing four [Online Mendelian Inheritance in Man (OMIM)] genes of PROS1, ARL13B, NSUN3 and EPHA6. Metaphase fluorescence in situ hybridization (FISH) analysis confirmed 30% (6/20 cells) mosaicism for the sSMC(3) in the blood lymphocytes. Conclusion: aCGH and FISH analyses are useful for perinatal investigation of a prenatally detected sSMC. Keywords: aCGH, Chromosome 3, FISH, Prenatal diagnosis, Small supernumerary marker chromosome